Age-specific transmission dynamic of mumps: A long-term large-scale modeling study in Jilin Province, China - Yang, Tianlong; Wang, Yao; Zhao, Qinglong; Guo, Xiaohao; Yu, Shanshan; Zhao, Zeyu; Deng, Bin; Huang, Jiefeng; Liu, Weikang; Su, Yanhua; Chen, Tianmu (Frontiers in Public Health, 2022)
Objectives: Despite the adoption of a new childhood immunization program in China, the incidence of mumps remains high. The aim of this study was to describe the epidemiological characteristics of mumps in Jilin Province from 2005 to 2019 and to assess the transmissibility of mumps virus among the whole population and different subgroups by regions and age groups. Methods The Non-age-specific and age-specific Susceptible–Exposed–Pre-symptomatic–Infectious–Asymptomatic–Recovered (SEPIAR) models were fitted to actual mumps incidence data. The time-varying reproduction number (Rt) was used to evaluate and compare the transmissibility. Results: From 2005 to 2019, a total of 57,424 cases of mumps were reported in Jilin Province. The incidence of mumps was the highest in people aged 5 to 9 years (77.37 per 100,000). The two SEPIAR models fitted the reported data well (P < 0.01). The median transmissibility (Rt) calculated by the two SEPIAR models were 1.096 (range: 1.91110-5 - 2.192) and 1.074 (range: 0.033 - 2.114) respectively. The age-specific SPEIAR model was more representative of the actual epidemic of mumps in Jilin Province from 2005-2019. Conclusions: For mumps control, it is recommended that mumps-containing vaccines (MuCV) coverage be increased nationwide in the 5-9 years age group, either by an mumps vaccine alone or by a combination of vaccines such as measles-mumps-rubella (MMR) vaccine. The coverage of vaccines in Jilin Province should be continuously expanded to establish solid immunity in the population. China needs to redefine the optimal time interval for MuCV immunization.